The impacts and challenges of COVID-19 in the favelas and the issue of (in)visibility (Research, Society and Development, 2022)
Objective: To identify evidence in the literature about the impacts and challenges that COVID-19 has caused in favelas. Methods: Integrative literature review, which sought publications from the year 2020 in the CAPES/MEC Journal Portal, in SciELO and Pubmed with the descriptors and their combinations in Portuguese and English: “Favelas” and “Covid-19”. Results: The authors point out impacts in several areas in the lives of the population living in slums, ranging from greater risks of contamination due to overcrowding and damage to health, nutritional status, as this population has its sources of income impaired and issues of a social nature, as occurred with the children who did not go to school and have lunch. Conclusion: The challenges facing COVID-19 are great, among them the social markers of difference, the difficulties in accessing health care and the lack of income for basic expenses.